The relationship of Mindfulness with Psychological flow for students of the College of Education for Pure Sciences 2018 - Dr. Khowla Hassan Hmood, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order for the student to be able to perform the proper and required manner, he must have the ability to mentally visualize the required skills, and this depends on the matching process. It is the process in which the new experience is adapted and modified with the experiences previously stored in the cognitive construction. The decrease in the level of individual’s psychological flow negatively affects the low level of performance, its decline, the weakness of focus and the loss of fluidity in practice. This tendency reveals a lot of positive thoughts after there was no control over negative thoughts, including the internal psychological state that makes the learner feel autistic and fully focused with what he is doing and the enthusiasm towards activities with a general sense of success in dealing with these activities. This is called psychological flow. This condition is related to the state of optimal learning, which Mihaly Shikzentemali described as a state of focus that rises to the level of absolute absorption. The current study aimed to identify the level of mental alertness and psychological flow among the fourth stage students of the College of Education for Pure Sciences at the University of Basra, and to examine the correlational relationship between them. The study adopted the relational descriptive approach. The study sample was composed of (135) male and female students, of whom (38) Male and 97 male students from the fourth stage of the College of Education for Pure Sciences in the academic year 2018/2019. They were chosen by a simple random method. Forrealizing the study objectives, two scales were used: the Mindfulness Scale (Langer), which was translated by both Al Mamouri and Abd 2016 and the Psychological Flow Scale (Al-Obaidi 2016). The results indicated that the sample members possessed an increasing level of mental alertness and psychological flow as well, indicating that there were no statistically significant differences at the level of mindfulness and psychological flow attributable to the gender variable.On the other hand, the results point out a statistically significantpositive correlation among mindfulness and psychological flow. In light of its conclusions, the study recommended a number of recommendations, including: Providing extension programs to increase mental alertness and psychological flow.